Class management implementation to boost the standard of teaching teachers - Lestari, Lindah; Fitria, Happy; Rohana, Rohana (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
The purpose of this study was to describe the implementation of the management of the classroom in order to improve the teaching quality of SMA Negeri 1 Babat Supat teachers. The principal and teachers were the sources of data for this research. Techniques for data gathering: 1) observation, (2) interviews, (3) documentation. Techniques for Data Analysis (1) data reduction, (2) presentation of data, (3) verification of data. The results of the observations of the researcher included: 1) Learning Implementation Plan (RPP), 2) Teacher appearance, 3) Opening and closing teacher activities, 4) Teacher activities varying learning stimuli, 5) Teacher activities questioning skills, and 6) Reinforcement teacher activities are said to be good because they refer to the components of the K13 curriculum.The barriers faced by this study were: (1) students did not pay attention to the material; (2) a limited number of supporting media; (3) the learning environment is not conducive; (4) students are usually passive in answering questions; (5) heterogeneous students are less concerned with education; (6) instilling character in students (lack of discipline).